2006
DOI: 10.1007/s00114-006-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Parasitoid-induced mortality of Araneus omnicolor (Araneae, Araneidae) by Hymenoepimecis sp. (Hymenoptera, Ichneumonidae) in southeastern Brazil

Abstract: All species included in the Polysphincta genus-group develop as ectophagous parasitoids of active spiders, killing their hosts prior to pupation. However, little information regarding natural history and ovipositing behavior of most species are available. In this study we inspected 85 webs of Araneus omnicolor to evaluate the frequency of parasitism and host size preferences of the wasp Hymenoepimecis sp. We also described the web characteristics of normal and parasitized spiders and the wasp ovipositing behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 8 publications
3
55
1
8
Order By: Relevance
“…The cocoon web constructed by M. biggiba resembles those induced by other Hymenoepimecis (Gonzaga et al 2010) and Acrotaphus wasp parasitism (Gonzaga and Sobczak 2011) by the presence of a dense and irregular tangle of non-sticky threads with several points of contact with the surrounding vegetation. The absence of the normal dome shaped portion and the high number of condensed support threads consists of a physical barrier that probably protects the cocoon and enhances the stability of the web.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The cocoon web constructed by M. biggiba resembles those induced by other Hymenoepimecis (Gonzaga et al 2010) and Acrotaphus wasp parasitism (Gonzaga and Sobczak 2011) by the presence of a dense and irregular tangle of non-sticky threads with several points of contact with the surrounding vegetation. The absence of the normal dome shaped portion and the high number of condensed support threads consists of a physical barrier that probably protects the cocoon and enhances the stability of the web.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies have described behavioral manipulations of spiders by the clade of koinobiont ectoparasitoid wasps of the Polysphincta genus-group (hereafter polysphinctine wasps) (Ichneumonidae: Pimplinae) (Gonzaga and Sobczak 2007, Matsumoto 2009, Korenko and Pekár 2011, Eberhard 2013, Sobczak et al 2014, Kloss et al 2016. Eberhard (2010) proposed that psychotropic substances released by wasp larva are the driving force behind behavioral manipulations of host spiders, but no additional studies have confirmed this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The species are characterised by the presence of a pocket-like structure on the pronotum, mesopleuron with carina epicnemial vestigial or absent, absence of the vein 3 rs-m in fore wing (Gauld, 1991), colour yellowish brown and large ocelli (Gauld and Dubois, 2006). All known species are koinobiont parasitoids of adult spiders of the family Nephilidae, Tetragnathidae and Araneidae (Fincke et al, 1990;Eberhard, 2000;Gauld, 2000;Gonzaga and Sobczak, 2007;Gonzaga et al, 2010). Despite this wide geographical distribution, little is known on host identities.…”
Section: Introductionmentioning
confidence: 99%